LEGAL POLICY OF INDONESIA’S AIR TRANSPORTATIONS HUMAN RESOURCES DEVELOPMENT IN FACING ASEAN ECONOMIC SOCIETY 2015 - Lestari, Endang Puji (UI Scholars Hub, 2016)
Legal policy of development and the provision of law flight human resources belong to national transportation policy subs-system. Legal policy contained in Act No. 7 of 2007 about RPJP puts the development of air transportation as one of the parts of the national facilities and infrastructure development. In the regime of flight law, human resources management is arranged in separated sections that belong to the national system development. The scope of human resources development and setting provision are as follow, human resources planning (manpower planning), education and training, expansion of employment opportunities, as well as surveillance, monitoring, and evaluation. The politic of legislated development setting and the provision of human resources that are made through delegated legislation above require further policy in form of three ministerial regulations as follow, ministerial regulation of the human resources provision and development in flight field, ministerial regulation of education and training in flight training, and ministerial regulation of competency certificate, licensee and training program.The writer advices the transportation ministry to realize in short time those three ministerial regulations which already have basic delegated delegation as the solution to face ASEAN open sky policy.